1993
DOI: 10.1002/eqe.4290220507
|View full text |Cite
|
Sign up to set email alerts
|

A modified static procedure for the design of torsionally unbalanced multistorey frame buildings

Abstract: SUMMARYSeismic building codes include design provisions to account for the torsional effects arising in torsionally unbalanced (asymmetric) buildings. These provisions are based on two alternative analytical procedures for determining the design load for the individual resisting structural elements. A previous study has shown that the linear elastic modal analysis procedure may not lead to conservative designs, even for multistorey buildings with regular asymmetry, when such structures are excited well into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
6

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
1
17
0
6
Order By: Relevance
“…In recent years, evaluation of the inelastic response of multi-storey systems has become more feasible due to development of powerful computational tools; therefore, checking and improving of previous results from single-storey models is believed to be crucial. Within this area of research, Duan and Chandler (1992) and Chandler and Duan (1992), as well as De La Llera and Chopra (1996), have recently analysed multi-storey asymmetric buildings with shear-type frames. Unfortunately, such models, which present a convenient simplified behaviour, consider that plastic hinges may occur at the ends of columns only and, therefore, they allow the investigation of buildings characterised uniquely by undesidered storey collapse mechanisms.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent years, evaluation of the inelastic response of multi-storey systems has become more feasible due to development of powerful computational tools; therefore, checking and improving of previous results from single-storey models is believed to be crucial. Within this area of research, Duan and Chandler (1992) and Chandler and Duan (1992), as well as De La Llera and Chopra (1996), have recently analysed multi-storey asymmetric buildings with shear-type frames. Unfortunately, such models, which present a convenient simplified behaviour, consider that plastic hinges may occur at the ends of columns only and, therefore, they allow the investigation of buildings characterised uniquely by undesidered storey collapse mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…Because of such an evidence, large research efforts have been devoted to examining effects of the lateral-torsional coupling on building seismic behaviour (Goel and Chopra, 1990;De Stefano et al, 1993, 1998De Stefano and Rutenberg, 1999) and to developing and proposing design procedures (Goel and Chopra, 1990;Chandler and Duan, 1992;Duan and Chandler, 1992;Tso and Zhu, 1992;Zhu and Tso, 1992; aimed at providing both plan-regular and plan-irregular systems with a similar level of seismic protection. To this purpose, most studies on seismic response of asymmetric structures have analysed response of single-storey models (Goel and Chopra, 1990;Tso and Zhu, 1992;Zhu and Tso, 1992;De Stefano et al, 1993, 1998De Stefano and Rutenberg, 1999; representing the most extreme idealisation of plan irregular buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at obtaining a simple evaluation of the inelastic analysis of asymmetric structures, Chandler and Duan (1992) adopted a multi-storey shear-type model, i.e., a scheme with infinitely stiff beams. Unfortunately, as underlined by other researchers (Moghadam and Tso 1996;Anagnostopoulos 2003, 2005), it is simple to investigate the behaviour of this model but not very realistic.…”
Section: Models For Multi-storey Asymmetric Buildingsmentioning
confidence: 99%
“…Much research has been carried out to find ways to improve the static method by means of design eccentricities (Goel and Chopra 1990;Chandler and Duan 1992;Duan and Chandler 1992;Tso and Zhu 1992;Zhu and Tso 1992). Two eccentricities are generally proposed to obtain satisfactory seismic performance of asymmetric structures, the first aiming at ensuring elastic behaviour during moderate earthquakes and the second at limiting maximum ductility demands to the demands of in-plan regular buildings in the event of strong ground motions.…”
mentioning
confidence: 99%
“…Their results indicated that the effects of lateral-torsional coupling on the response of a multistorey eccentric building and its associated one-storey system are similar. Duan and Chandler [26,27] further reported that a single-storey structural model is not Shock and Vibration 3 on its own sufficient to investigate completely the inelastic torsional effects in multistorey regularly asymmetric buildings which are unlike elastic studies. Anagnostopoulos et al [28] pointed out that conclusions based on the widely used simplified, one story, eccentric systems of the shear-beam type, to actual, nonsymmetric buildings and consequent assessments of the pertinent code provisions, can be quite erroneous, unless special care is taken to match the basic properties of the simplified models to those of the real buildings.…”
Section: Introductionmentioning
confidence: 99%